Perkolacija - Rot, Miha (Matrika, 2018)
The article presents basics of percolation theory and uses simple examples to demonstrate concepts that enable a description of systems with phase trasitions that would otherwise be too difficult to deal with. Real world examples of percolation theory usage are described in the latter part of the article, specifically cell growth ordering and weather system analysis.
Keywords: percolation; perkolacija